Effects of rapid maxillary expansion and functional orthodontic treatment in children with sleep disordered breathing: a systematic review - Magdalena Piełunowicz; Jacek Kotuła; Krzysztof Kotuła; Mieszko Więckiewicz; Joanna Lis; Beata Kawala; Anna Ewa Kuc; Michał Sarul (BMC Oral Health)
Abstract Background Sleep disordered breathing (SDB) in children, characterized by sleep apnea episodes or other episodic or persistent breathing disorders, can be associated with the occurrence of some malocclusions. However, there are few clinical studies on the correlation of the occurrence of malocclusions and the effects of their treatment with reduction of SDB symptoms. Therefore, we conducted a systematic review of this topic, focusing on the population of children during the age of tooth replacement demanding orthopedic treatment for maxillary transverse growth deficiency and anterior mandibular growth modification. This systematic review seeks to assess effect on quality of sleep resulting from Rapid Maxillary Expansion and functional orthodontic treatment in patients with SDB and morphological changes occurring in the oral cavity and upper respiratory tract contributing to the reduction of SDB symptoms. Methods The review was conducted in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses 2020 (PRISMA 2020). The study design was defined in the PICO format—Population (P): non-syndromic prepubertal and adolescent patients requiring orthodontic treatment, who additionally have coexisting sleep disorders; Intervention (I): Orthodontic treatment of malocclusion with differentiated appliances; Comparison (C): evaluation of Apnea Hypopnea Index (AHI) and sleep questionnaires pre and post treatment; Outcome (O): effect of orthodontic treatment on sleep quality. Search filters included the time of the publication—articles of 11 last years and publications that was published in English. The following variables were established for the selected articles: sample size, demographic characteristics, orthodontic treatment methods, type of study, AHI (Apnea–Hypopnea Index) parameter. The following scientific databases were searched: PubMed, Embase, Cochrane Central. The articles were analyzed for risk of bias and quality using the Risk Of Bias In Non-randomized Studies—of Interventions (ROBINS-I) protocol. Results After entering the keywords, 3,252 articles were retrieved. Of these, 16 articles were deemed eligible for systematic review and were thoroughly analyzed, of which 11 articles did not meet the inclusion criteria. Five articles (n = 248 individuals, 163 girls and 124 boys) aged 8–12.5 years, mean age 10.6, were included in the review. In 124 patients with class II malocclusions or mandibular retrognathia, a modification of the anterior growth of the mandible was used using Twin-Block appliances with the possible use of class II traction, and in 124 patients with bilateral crossbite, the Rapid Maxillary Expansion (RME) method was used. The quality of upper airway patency and sleep quality related to SDB was examined using polysomnographic analysis, polygraphy analysis, cephalometric studies and questionnaires. Conclusions The literature review suggests that orthodontic treatment may improve sleep quality, alleviate symptoms of SDB, and enhance sleep parameters however one article does not support this thesis. A close correlation between these phenomena has not yet been fully established. The current review is a good starting point for introducing simpler methods of examining the quality of sleep, in children, which requires further research on this topic. Registration CRD42024565669.